Unusual presentation of rheumatoid arthritis in a 106‐year‐old woman: A rare case report - Ali ALQazzaz; Faiq I. Gorial; Ahmed Dheyaa Al‐Obaidi; Mustafa Najah Al‐Obaidi; Nabaa Ihsan Awadh; Hashim Talib Hashim (Clinical Case Reports)
Abstract By reporting this case, we hope to encourage medical professionals to concentrate on diagnosing old patients with unusual presentation of rheumatoid arthritis.